Analysis of the Need for Developing E-Modules Based on Problem-Based Learning on Heat Transfer Material for Middle School Students - Anida Chairatunnisa; Leni Marlina; Ketang Wiyono (Universitas Lambung Mangkurat, 2024)
To help students understand the learning process, e-module development for science instruction was crucial. The objectives of this study were to identify the learning resources that students use to comprehend the material in physics, identify the learning resources that need to be developed in physics learning, and describe the examination of needs for developing an e-module based on Problem-Based Learning (PBL) on heat transfer material at the junior high school level. This study (mixed method research) used both quantitative and qualitative methods. The research and development (R&D) technique employing a 4D model (define, design, development, and disseminate) was utilized in this study. However, it should be noted that only the define stage was addressed within the scope of this research. The primary objective was to collect data, for which 38 seventh-grade students from SMP Negeri 6 Palembang participated by responding to an online questionnaire. Analysis was conducted using a descriptive qualitative method. The findings from the questionnaire collection were utilized to develop two e-modules intended to aid in understanding physics learning materials, particularly those related to heat transfer. The implications suggested that resources such as e-modules were necessary for students to comprehend and learn physics concepts, especially those related to heat transfer. Additionally, various learning materials like textbooks, e-books, worksheets, and online media were identified as essential for effective physics education. The significance of creating e-modules rooted in problem-based learning to aid students in grasping physics content, particularly concerning heat transfer, was highlighted. Furthermore, the research underscored the necessity for developing various learning resources such as textbooks, e-books, worksheets, and online media for physics education. These findings could enhance curriculum development and teaching methodologies by providing insights into students' characteristics and requirements when studying heat transfer material.